Examining clinicians' concerns delivering telemental health interventions directly to autistic individuals during COVID-19. (June 2022) - Adams, Lucy; Adamo, Nicoletta; Hollocks, Matthew J.; Valmaggia, Lucia; Brewster, Aylana; Watson, Jennifer; Krisson, Maisie; Simonoff, Emily
Abstract: Background: The COVID-19 pandemic necessitated the adoption of telemental health (TMH). Pre-pandemic, clinicians had voiced many TMH concerns, but these had not been investigated with respect to autism spectrum disorder (ASD) even with it being known that there are distinct ASD-associated challenges for in-person mental health interventions. Method: A convenience sample of ( n = 55) clinicians completed an online survey regarding their perspectives of adopting TMH interventions in ASD, with closed- and open-answered questions. Quantitative and qualitative data were analysed descriptively/inferentially and via Content Analysis, respectively. Results: Multiple clinicians endorsed each TMH challenges/barrier previously identified as concerns in the non-ASD literature. However, overall levels of concern over challenges/barriers were low, and challenges were more likely to be predicted than experienced and considered to be case/presentation specific. Challenges that were considered ASD-specific included the exacerbation of those associated with in-person delivery in ASD, alongside difficulties with trust and appropriate remote social behaviour. On average, clinicians indicated a preference for 50% TMH interventions post-pandemic. Clinicians' perceived technological competence and extent of professional experience with ASD were not significantly associated with levels of concern, nor number of experienced challenges, with TMH interventions in ASD. Conclusion: In support of the existing TMH literature, challenges/barriers were more likely to be predicted than experienced and were considered to be case/presentation-specific, though this may be more variable in ASD owing to the well-established marked heterogeneity in this population. Remote provision of interventions exacerbated in-person ASD-associated challenges, as predicted, but clinician-level factors appeared not to impact TMH perceptions. Highlights: First ASD study focused on routine and direct telemental health (TMH) interventions. First study to show that TMH concerns from non-ASD clinicians are as follows. Shared and experienced as challenges by clinicians supporting autistic individuals. Such as perceived inter-individual variability in suitability. Mostly considered addressable but at times intensified and added to in ASD.